Association between high-risk human papillomavirus infection female infertility - Hammood, Sarab Khlalaf; Mohammed, Farah Majid; Hassan, Maysaloon Fadhil (International Journal of Psychosocial Rehabilitation, 2020)
From a biological perspective, HPV is a very successful pathogen; that is, it can induce chronic infections without any systemic symptoms, allowing the host to periodically shed large amounts of transmissible virus to naïve individuals. A cross-sectional study was carried out in Kirkuk city-Iraq from June 2019 to the end of November 2019, including 200 women who attended to private clinics and suffering from infertility, and 100 controls (women without infertility). Five ml of blood was collected by vein puncture from each subject enrolled in this study. Blood samples were placed into sterile test tubes, the obtained sera were then aspirated using automatic micropipette and transferred into clean test tubes for detection of HPV16 and 18 E7 proteins by using ELISA technique. The study showed that the highest rate of HPV E7 proteins (29.5%) was detected in women with infertility comparing with healthy women (12%) with highly significant relation of HPV with infertility ( P. value: 0.05). The highest mean of BMI were recorded among non-infertile women compared with infertile women (23.92 ± 1.55 v.s 25.36±1.99 kg/m2), the result was significant. There was no significant difference regarding to LH, FSH, E2, progesterone level between infertile and control group women (p: < 0.05). It was concluded that female infertility was associated with HPV infection specially with HPV 16 and 18 serotypes.